2020
DOI: 10.3171/2020.5.jns201421
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of robotic-assisted carotid stenting and manual carotid stenting through the transradial approach

Abstract: OBJECTIVEThe objective of this study was to demonstrate the feasibility and safety of CorPath GRX robotic-assisted (RA) transradial (TR) carotid artery stenting (CAS) compared with manual TR CAS.METHODSThe authors conducted a retrospective analysis of a prospectively maintained database and identified 13 consecutive patients who underwent TR CAS from June 2019 through February 2020. Patients were divided into 2 groups: RA (6 patients) and manual (7 patients).RESULTSAmong 6 patients in the RA group with a mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Some studies have shown that transfemoral carotid artery stenting (TCAR) can reduce the incidence of perioperative embolic complications in CAS, especially in high-risk patients requiring treatment with CAS, and has a low incidence of local complications, neurological events, myocardial complications, and mortality during the early postoperative period, and is considered an acceptable alternative in patients treated with CAS[ 26 - 29 ]. Furthermore, transradial carotid artery stenting has demonstrated feasibility and safety in CAS[ 30 - 32 ]. Recently, robotic-assisted CAS has been shown to be technically feasible; however, further studies are warranted to properly establish the safety and benefits of this technique[ 30 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that transfemoral carotid artery stenting (TCAR) can reduce the incidence of perioperative embolic complications in CAS, especially in high-risk patients requiring treatment with CAS, and has a low incidence of local complications, neurological events, myocardial complications, and mortality during the early postoperative period, and is considered an acceptable alternative in patients treated with CAS[ 26 - 29 ]. Furthermore, transradial carotid artery stenting has demonstrated feasibility and safety in CAS[ 30 - 32 ]. Recently, robotic-assisted CAS has been shown to be technically feasible; however, further studies are warranted to properly establish the safety and benefits of this technique[ 30 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, transradial carotid artery stenting has demonstrated feasibility and safety in CAS[ 30 - 32 ]. Recently, robotic-assisted CAS has been shown to be technically feasible; however, further studies are warranted to properly establish the safety and benefits of this technique[ 30 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar research group conducted a retrospective comparison of transradial robot-assisted carotid stent placement with manual stent placement and found that the mean procedural duration was significantly longer while using the robot (85.0 [SD, 14.3] versus 61.2 [SD, 17.5] minutes), but there was no significant difference in other procedural characteristics such as fluoroscopy time, contrast dose, radiation exposure, catheter exchanges, technical success, transfemoral conversion, and complications. 54 Nogueira et al 55 also recently treated 4 patients with severe symptomatic carotid stenosis and achieved technical and procedural success. All steps of the procedure were completed by the robotic system except for navigation and deployment of the stent, which is currently incompatible.…”
Section: Clinical Applications Of Robotic Neurointerventionmentioning
confidence: 99%
“…One of the major goals of robotic endovascular systems is to increase efficiency and decrease procedural time; yet, early research indicates prolonged procedural time when using the robot. 54 It is unclear whether this issue is entirely due to inherent deficiencies of current robots or more related to limited operator experience. Clearly, a standardized training curriculum is needed to optimize physician interaction with robotic systems.…”
Section: Limitationsmentioning
confidence: 99%
“…1,2 Additionally, a great merit of robotic surgeries is the ability to perform them at remote locations, which would essentially provide lifesaving procedures to patients who are unable to present to a cerebrovascular center in a timely fashion. [2][3][4][5][6] Historically, robots were largely designed for other surgical specialties, mainly interventional cardiology; 1 it was more recently that they were engineered to assist in neurosurgical procedures such as depth electrode implantation for epilepsy, and minimally invasive spine surgeries. 7,8 The CorPath GRX (Corindus Inc.) robot-assisted platform is the latest robotic system initially designed for interventional cardiology procedures.…”
mentioning
confidence: 99%